A comparison of the antifouling performance of air plasma spray (APS) ceramic and high velocity oxygen fuel (HVOF) coatings for use in marine hydraulic applications. Issue 5 (28th May 2018) - Piola, Richard; Ang, Andrew S. M.; Leigh, Matthew; Wade, Scott A.
Abstract: Maritime hydraulic components are often exposed to harsh environmental conditions which can lead to accelerated deterioration, reduced function, equipment failure and costly repair. Two leading causes of maritime hydraulic failure are biofouling accumulation and corrosion. This study examined the antifouling performance of three candidate replacement high velocity oxygen fuel (HVOF) coatings relative to the performance of the current baseline air plasma spray (APS) ceramic coating for protection of hydraulic actuators. Following 20 weeks immersion at tropical and temperate field exposure sites, the control APS ceramic accumulated significantly greater levels of biofouling compared to the HVOF coatings. More specifically, the magnitude of growth of real-world nuisance hard fouling observed on in-service hydraulic components (eg calcareous tubeworms and encrusting bryozoans) was significantly greater on the APS ceramic relative to HVOF coatings. Possible explanations for the observed patterns include differences in surface topography and roughness, the electrochemical potential of the surfaces and the colour/brightness of the coatings.